Rationale and design of the multidisciplinary team IntervenTion in cArdio-oNcology study (TITAN). Issue 1 (December 2016) - Pituskin, Edith; Haykowsky, Mark; McNeely, Margaret; Mackey, John; Chua, Neil; Paterson, Ian
Abstract Background Cancer is the leading cause of premature death in Canada. In the last decade, important gains in cancer survival have been achieved by advances in adjuvant treatment. However, many oncologic treatments also result in cardiovascular "toxicity". Furthermore, cardiac risk factors such as hypertension, dyslipidemia, and diabetes mellitus are known to contribute to the progression of cardiac damage and clinical cardiotoxicity. As such, for many survivors, the risk of death from cardiac disease exceeds that of recurrent cancer. While provision of care by multidisciplinary teams has been shown to reduce mortality and hospitalizations among heart failure patients, the effect of assessments and interventions by multidisciplinary specialists in cancer patients receiving cardiotoxic chemotherapy regimens is currently unknown. Accordingly, we will examine the effect of a multi-disciplinary team interventions in the early assessment, identification and treatment of cardiovascular risk factors in cancer patients receiving adjuvant systemic therapy. Our main hypothesis is to determine if the incidence of LV dysfunction in cancer patients undergoing adjuvant therapy can be reduced through a multidisciplinary team approach. Methods/design This is a randomized study comparing intensive multidisciplinary team intervention to usual care in the prevention of LV remodeling in patients receiving anthracycline or trastuzumab-based chemotherapy. Main objectives include early detection strategies for cardiotoxicity using novel biomarkers that reflect myocardial injury, remodeling and/or dysfunction; early identification and intensive treatment of cardiovascular risk factors; and early intervention with supportive care strategies including nutritional and pharmacist counselling, exercise training and cardiology team support. Secondary objectives include correlation of novel biomarkers to clinical outcomes; correlation of multidisciplinary interventions to adverse clinical outcomes; relationship of multidisciplinary interventions and chemotherapy dose density; preservation of lean muscle mass; and patient reported outcomes (symptom intensity and quality of life). Discussion Cardiac toxicity as a result of cancer therapies is now recognized as a significant health problem of increasing prevalence. To our knowledge, TITAN will be the first randomized trial examining the utility of multidisciplinary team care in the prevention of cardiotoxicity. We expect our results to inform comprehensive and holistic care for patients at risk for negative cancer therapy mediated sequelae. Trial registration ClinicalTrials.gov, NCT01621659 Registration Date 4 June 2012.